The relationship between human resource practices and work engagement - Kogilavani, Veraiyah (2023)
The purpose of this research is to investigate the relationship between human resource practices and work engagement. This is a correlational study, as its objective is to analyse the relationship between different variables. The population for this study consists of employees from a manufacturing company located in Kuala Kangsar, Perak, with a total target population of 439 employees. This study used simple random sampling technique to choose the respondents. This study also used quantitative research approach with cross-sectional study. Besides that, data for this study were obtained by distributing questionnaire via google form to sample size of 203 employees that has been chosen from simple random technique. The response rate of this study is 93.5%, which has been used for further analysis. To examine the data Statistical Package for Social Science (SPSS) version 27 was used. The result of Pearson’s correlation analysis shows that career advancement, employee participation, performance feedback, job security, rewards and recognition and training and development have positive and significant relationship with work engagement. The multiple regression result shows employee participation, performance feedback and training and development has no significant influence towards work engagement. Meanwhile, career advancement, job security and rewards and recognition have positive significant relationship with work engagement in a manufacturing company. This study also has indicated on practical implication, theoretical implications and limitation while performing this study. This study also suggested recommendations for future researchers who are interested in studying the relationship between HR practices and work engagement.